Time constraints on magmatism, mineralisation and metamorphism at the Falun base metal sulphide deposit, Sweden, using U-Pb geochronology on zircon and monazite - Kampmann, Tobias; Stephens, Michael; Ripa, Magnus; Hellström, Fredrik; Majka, Jarosław (Precambrian Research, 2016)
U–Th–Pb (zircon and monazite) ion probe data have provided constraints on the timing of emplacement and metamorphism of magmatic rocks close to the Palaeoproterozoic, Falun base metal sulphide deposit in the Bergslagen lithotectonic unit, Fennoscandian Shield, Sweden, and, thereby the timing of mineralisation. Hydrothermal alteration and mineralisation at Falun are constrained to a short interval of several million years between a 207Pb/206Pb weighted average age of 1894 ± 3 Ma for a rhyolitic sub-volcanic rock in the felsic volcanic to sub-volcanic host rock suite, and a 207Pb/206Pb weighted average age of 1891 ± 3 Ma for a post-sulphide, porphyritic dacite dyke. Magmatism also included the emplacement of granite plutons with igneous crystallization ages of 1894 ± 3, 1894 ± 2 Ma and 1893 ± 3 Ma. The felsicsub-volcanic to volcanic activity and the emplacement of dacite dykes and granite plutons overlap in age within their respective analytical uncertainties, indicating hydrothermal alteration and sulphide mineralisation inside a narrow time span of intense magmatic activity, and burial of the supracrustal rocks.Two distinct patchy and homogeneous metamorphic monazite types in a felsic volcanic rock around and hydrothermally altered rocks at the Falun deposit yield 207Pb/206Pb weighted average ages of 1831 ± 8 Ma and 1822 ± 5 Ma, respectively. These ages fall well within the temporal range of a younger1.84–1.81 Ga (M2) metamorphic episode during the 2.0–1.8 Ga Svecokarelian orogeny, with the older episode (M1) inside the Bergslagen lithotectonic unit at around 1.86 Ga. This shows the major influence of the M2 event in the north-western part of this unit, leading to a complete resetting of the U–Th–Pb isotopesystem in monazite. Validerad; 2016; Nivå 2; 20151014 (tobkam) Structural evolution, hydrothermal alteration and tectonic setting of the Falun base metal and gold deposit, Bergslagen region, Sweden